Dynamics of MBD2 deposition across methylated DNA regions during malignant transformation of human mammary epithelial cells. Issue 12 (24th May 2015) - Devailly, Guillaume; Grandin, Mélodie; Perriaud, Laury; Mathot, Pauline; Delcros, Jean-Guy; Bidet, Yannick; Morel, Anne-Pierre; Bignon, Jean-Yves; Puisieux, Alain; Mehlen, Patrick; Dante, Robert
Abstract: DNA methylation is thought to induce transcriptional silencing through the combination of two mechanisms: the repulsion of transcriptional activators unable to bind their target sites when methylated, and the recruitment of transcriptional repressors with specific affinity for methylated DNA. The Methyl CpG Binding Domain proteins MeCP2, MBD1 and MBD2 belong to the latter category. Here, we present MBD2 ChIPseq data obtained from the endogenous MBD2 in an isogenic cellular model of oncogenic transformation of human mammary cells. In immortalized (HMEC-hTERT) or transformed (HMLER) cells, MBD2 was found in a large proportion of methylated regions and associated with transcriptional silencing. A redistribution of MBD2 on methylated DNA occurred during oncogenic transformation, frequently independently of local DNA methylation changes. Genes downregulated during HMEC-hTERT transformation preferentially gained MBD2 on their promoter. Furthermore, depletion of MBD2 induced an upregulation of MBD2-bound genes methylated at their promoter regions, in HMLER cells. Among the 3, 160 genes downregulated in transformed cells, 380 genes were methylated at their promoter regions in both cell lines, specifically associated by MBD2 in HMLER cells, and upregulated upon MBD2 depletion in HMLER. The transcriptional MBD2-dependent downregulation occurring during oncogenic transformation was also observed in two additional models of mammary cell transformation. Thus, the dynamics of MBD2 deposition across methylated DNA regions was associated with the oncogenic transformation of human mammary cells.